Analysis of blood flow features in the curved artery in the presence of differently shaped hybrid nanoparticles - K.N. Asha; Neetu Srivastava (Partial Differential Equations in Applied Mathematics)
This study combines the analysis of blood flow in curved arteries with the exploration of how differently shaped hybrid nanoparticles impact these flows, offering potential applications in biomedical engineering, nanomedicine, and the treatment of cardiovascular diseases. The study explores how different fluid flow parameters and nanoparticle shapes affect the velocity, wall shear stress, Nusselt number and temperature profiles in a curved artery. The analytical approach is employed determine the solutions of the governing equations, leading to solutions for velocity, wall shear stress, Nusselt number, and temperature distributions, while taking into account the effects of slip at the boundary. The shape of nanoparticles affects all the velocity, wall shear stress, temperature and the Nusselt number within a stenotic curved artery. This work provides a comprehensive overview of the mathematical model, its solutions, and visual data, offering valuable insights for researchers and medical professionals on the potential applications of hybrid nanoparticles in managing stenotic blood flow.